Pengaruh Motivasi dan Perilaku Keuangan yang Di Moderasi Oleh Literasi Keuangan Terhadap Keputusan Investasi Mahasiswa Pascasarjana - Annisa, Dian (JURNAL ILMIAH EDUNOMIKA, 2025)
Investment plays an essential role in students’ financial management, especially in achieving long-term objectives. Nevertheless, investment choices are shaped by both internal and external influences. This research investigates how financial motivation and financial behavior affect the investment decisions of postgraduate students, with financial literacy acting as a moderating factor. The study applied a quantitative method by distributing surveys to 80 postgraduate students at Bina Darma University. Data were gathered using questionnaires and processed through SmartPLS analysis. The results indicate that financial motivation and financial behavior each have a positive influence on investment decisions. In addition, financial literacy significantly moderates the relationship between financial motivation and investment decisions, though it does not reinforce the effect of financial behavior. These findings underscore the relevance of improving students’ financial literacy to maximize the role of motivation in investing and highlight the necessity of continuous financial education to foster rational and strategic decision-making. Keywords: Motivation; Financial Behavior; Financial Literacy; Investment Decisions; Postgraduate Students